Pay Structure, Female Representation and the Gender Pay Gap among University Professors - Doucet, Christine; Smith, Michael; Durand, Claire (Relations industrielles / Industrial Relations)

(untitled) (Département des relations industrielles de l’Université Laval, 2012)
SummaryIn this case study of faculty at a large Canadian research university we examine the extent to which the gender pay gap varies with the formalization of remuneration practices and female representation within units. We estimate the respective contributions to the gender pay gap of base pay, access to the rank of full professor, access to and amounts of market supplements, and Canada Research Chairs. These remuneration components differ in their degree of formalization. We also examine variations in the gender pay gap across departments with different proportions of females. The use of multilevel analysis allows for the estimation of the respective contributions of individual and institutional determinants of pay. Mixed support is found for the first hypothesis – that the magnitude of the gap varies with the degree of formalization in remuneration components. The second hypothesis that, all else being equal, the level of female representation in a given context is negatively related to remuneration is supported. Overall, the results are consistent with continuing female pay disadvantage, even in an ostensibly ‘progressive’ institutional context.